دراسة نمذجة ومحاكاة لتأثير التدرج الحراري في خزانين حراريين مختلفي الشكل على الأداء الحراري لأنظمة تسخين الماء الشمسية. - كنجو, لانا (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير التدرج الحراري في خزانين حراريين مختلفي الشكل على الأداء الحراري لأنظمة تسخين الماء الشمسية، وقد تم ذلك باستخدام برنامج المحاكاة (TRNSYS). حيث تم نمذجة نظامي تسخين ماء شمسيين يستخدمان خزانين حراريين شاقوليين أحدهما اسطواني الشكل (CV)، والآخر ذي مقطع عرضي مربع الشكل (UCS). تم دراسة ظاهرة التدرج الحراري في الخزانين الحراريين للنظامين في ظروف متماثلة (حمل الماء الساخن، الشروط المناخية،...الخ). تم أيضاً دراسة تأثير بعض المتغيرات على تحقيق هذه الظاهرة وبالمحصلة على الأداء الحراري لنظامي تسخين الماء الشمسيين الذي يُعبّر عنه المردود ونسبة التغطية الشمسية، ومن ثم أجريت المقارنة بين النظامين المدروسين. أظهرت نتائج المحاكاة المنجزة في هذا البحث لمدة عام كامل بخطوة زمنية قدرها ساعة واحدة للنظامين المدروسين، أن الخزان الحراري الاسطواني الشكل كان أفضل بقليل في تحقيق التدرج الحراري من الخزان ذي المقطع العرضي المربع الشكل ومن أجل جميع المتغيرات المدروسة (الفرق في نسبة التغطية الشمسية حوالي 0.5 %). كما أظهرت النتائج أن أفضل عدد للطبقات الحرارية ضمن الخزانين الحراريين هو (n=10)، وأنه من أجل حجم معين مدروس (300 lit) للخزان الحراري كانت أفضل نسبة ارتفاع للخزان إلى البعد المميز لمقطعه هي (H/L = 3). ومن أجل الحجم المدروس نفسه كان أفضل ارتفاع ثابت لمدخل الماء الساخن إلى الخزان للنظام الأول (CV) هو (0.9 m) وللنظام الثاني (UCS) هو(0.7 m)، ولكن استخدام مدخل متغيّر الارتفاع أوتوماتيكياً كان هو الأفضل لكلا النظامين بحيث كانت الزيادة في نسبة التغطية الشمسية عن حالة المدخل الثابت الارتفاع بحوالي(1 %). This research aims to study the influence of thermal stratification in two different shapes of storage tank on thermal performance of solar water heating systems, and this has been done by using simulation program (TRNSYS). Where two solar water heating systems have been modeled using two vertical storage tanks, one of them had a cylindrical form (CV), and the other one had a square cross section form (UCS). The study of the phenomenon of thermal stratification in the two storage tanks of the systems has been done in identical conditions (hot water load, weather conditions, ...etc). Another study has been done, it was the effect of some variables on performing this phenomenon, and accordingly on the thermal performance of the two solar water heating systems which have been expressed by thermal efficiency and solar cover ratio, and then a comparison between the two systems has been done. Results of simulations in this research, which have been done for one year by one hour as a step time on the two systems, showed that the cylindrical storage tank was little better in performing the thermal stratification than the square cross section tank for all the variables studied (difference in solar cover ratio about 0.5%). Also results showed that the best number of thermal layers within the storage tanks was (n=10), and for a specific size studied of storage tank (300 lit) the best ratio of height the storage tank to the distinguished dimension of its section was (H/L=3). However, for the same specific size studied, the best fixed height of hot water entrance to the first system storage tank (CV) was (0.9 m) and for the second system (UCS) was (0.7 m). But, using automatically changed height of entrance was the best for both systems so that the increase in solar cover ratio of the case of fixed height was about (1%).